A Survey on Computer Graphics Technology with A Focus on Its Applications in Bio Medical Imaging - K. Arumugam,; S. Saravana kumar, (AG Volumes, 2022)
Humans are able to process visual information more quickly than any other kind of information. Recognization, monitoring, as well as surveillance are all made possible by image sensors. There are a wide range of applications where networks of sight sensors are the best answer. Designers of image sensor nodes face architectural problems, like processing power, energy consumption, communication routes, as well as sensing capabilities. In this article, we'll go through the features and specifications of an image sensor node. A wireless sensor network image sensor node is developed and built. CMOS sensor, RF module, image acquisition unit, and power unit are all included in the system. Imaging sensors may benefit from more energy-efficient hardware management solutions. In this article, the issue of picture compression in sensor nodes is thoroughly examined.